RIGHT ALTERNATIVE RINGS WITH x(yz)−y(xz) IN THE CENTER - Reddy, K. Madhusudhan; Suvarna, K. (Italian Journal of Pure and Applied Mathematics, 2014)
In [1] it was proved that if R is a prime right alternative ring of char. ≠ 2, 3 with (R, R, U ) ⊆ U or S(x2, x, y) = 0, then either U = C or R is strongly (−1, 1). In this paper first we prove that if R is a prime right alternative ring with x(yz) - y(xz) ∈ U, then (R, R, U ) ⊆ U. Using this we prove that either U = C or R is strongly (−1, 1).